Treatment of second-degree burns with 0.2% Hyaluronic Acid: An integrative literature review (Research, Society and Development, 2023)
Second-degree burns affect the outer layer of the skin, known as the epidermis, and the underlying layer called the dermis. They can be caused by sources of heat, such as flames, hot liquids, or prolonged contact with hot surfaces. Effective treatment of second-degree burns is important to promote proper healing, prevent infections, and minimize the physical and emotional impact on patients. 0.2% hyaluronic acid has sparked interest in the treatment of second-degree burns due to its beneficial properties in tissue regeneration. This study is a literature integrative review, compiling information from published references to provide greater visibility and connect researchers to existing literature on the topic. This contributes to deepening knowledge on the subject and guiding future research. Scientific materials published in books, national and international journals, websites, and documents from entities related to scientific research were used. The literature review followed a systematic and comprehensive process, consisting of six stages: identification of the problem or research question, establishment of inclusion and exclusion criteria for studies, definition of information to be extracted from selected studies, evaluation of studies, interpretation of results, and presentation of the synthesis of knowledge. Databases such as SCIELO, LILACS, Public Medline, and Google Scholar were used to search for relevant articles and theses on the topic. The literature review highlighted the need for further studies on the research subject.